Language learning strategies employed by proficient EFL students in learning speaking skills - Azizi, Faniah Nur; Yusuf, Fazri Nur (JOALL (Journal of Applied Linguistics and Literature), 2024)
This study investigatres the language learning strategies utilized by two proficient EFL learners in learning speaking skills. The present descriptive case study probes and narrates the accounts of two proficient English speakers related to the language learning strategies they employed in learning speaking skills. The two proficient English speakers were perceived as credible and ellible sources for this study as they possess the required TOEFL score for proficient learners as indicated by the English Testing Service (ETS), which is around 543-627 in range. The data used in this study were obtained through four semi-structured interviews conducted via Zoom meetings with the participats. A document in the form of participants’ detailed learning schedules was also gathered to enhance data trustworthiness. Subsequently, the data collected were analysed thematically, generating seven categories of language learning strategies. Findings indicate that both participants utilized all seven strategies performed as the most frequently used strategy. It implies tht both participants often plan, arrange and evaluate their learning in advance. The study also found that few strategies were employed at the early stage of leanring and are no longer in use at present.